Digital health literacy in Norwegian patients with hip and knee arthroplasty: normative data from a cross-sectional study - Turid Rognsvåg; Ingrid K Nordmo; Ingvild B Bergvad; Anne M Fenstad; Ove Furnes; Anners Lerdal; Maren F Lindberg; Søren T Skou; Mona Badawy (Acta Orthopaedica, 2024)
Background and purpose: As digital health services become increasingly important in osteoarthritis treatment, understanding patients’ digital health literacy (eHL) is crucial, including those undergoing total hip and knee arthroplasty (THA/TKA). We primarily aimed to provide eHL norms in a representative group of Norwegian patients, and secondarily to examine the relationships between eHL and health-related quality of life (QoL). Methods: We invited 800 randomly selected THA/TKA patients from the Norwegian Arthroplasty Register to complete a paper-based questionnaire, which included sociodemographic variables. eHL was measured using the eHealth Literacy Questionnaire (eHLQ) with 7 domains: Using technology, Understand, Engage, Control, Motivation, Access, and Needs, scored from 1 (strongly disagree) to 4 (strongly agree). The EuroQol EQ-5D-5L measured health-related QoL. We used multivariable regression to examine relationships between eHL domains and health-related QoL controlling for sociodemographic variables. Results: Respondents’ (N = 383, 48%) mean age was 70 years (SD 9.0) and 246 (64%) were female. Mean eHLQ and the proportion of patients with low eHL (≤ 2.5) were Technology 2.7 (34%), Understanding 3.0 (14%), Engage 2.7 (28%), Control 3.2 (7.7%), Motivation 2.8 (35%), Access 2.8 (33%), and Needs 2.6 (46%). Low eHL correlated with older age and low education, but not with sex or type of surgery. Regression analyses showed that lower scores on the domains Technology, Engage, Control, Access, and Needs were associated with poorer QoL after adjusting for sociodemographic factors. Conclusion: About one-third of THA/TKA patients have low eHL, and low eHL was associated with poor QoL.